If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -5x = -9 + 3x Solving 4 + -5x = -9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + -5x + -3x = -9 + 3x + -3x Combine like terms: -5x + -3x = -8x 4 + -8x = -9 + 3x + -3x Combine like terms: 3x + -3x = 0 4 + -8x = -9 + 0 4 + -8x = -9 Add '-4' to each side of the equation. 4 + -4 + -8x = -9 + -4 Combine like terms: 4 + -4 = 0 0 + -8x = -9 + -4 -8x = -9 + -4 Combine like terms: -9 + -4 = -13 -8x = -13 Divide each side by '-8'. x = 1.625 Simplifying x = 1.625
| z^2+(1+i)z+2-i=0 | | 2z+2y=5y | | 9x+4=4-6x | | 6x-3=-2x+12 | | 2z+2y=5x | | 2x+2y=5z | | (x-2.9)(x+1.4)=0 | | 4x+2-3x+3=8 | | x^2+22x=3600 | | 2x^2-4=50+2x^2 | | -100x=-1000 | | 3x-9=5-4x | | 0.14=x(0.1+2x) | | 1.4e-8=x(0.1+2x) | | 96484*7x=67 | | 3x-2y=17x+4y=1 | | 3x-2y=17x+4y=1 | | 70-1.5h=5-20 | | 10x^2+9x-4=0 | | 10h+4=97 | | 5(x+4)-7(5-x)= | | X^2+2BX+1=0 | | 2(x-4)+27=3(3-x) | | 9m-16=64 | | 5y-14=13 | | -200+5.5p=102.50 | | -200+5.5p=-120.5 | | 2x^2+9x-20=0 | | -200+5.5p=-120.50 | | -200+5.5p=-35 | | X^2+6x-111=0 | | 6+2y=16+8y |